Do government subsidies stimulate firms' R&D efforts? Empirical evidence from China. Issue 2 (3rd May 2020) - Sun, Xiaohua; Yu, Runqun; Wang, Yun; Colombage, Sisira R. N.
ABSTRACT: Government subsidies have been one of the popular policy instruments to stimulate firms' R&D activities. We empirically investigate the impact of government subsidies on firms' R&D decisions of listed manufacturing firms in China. In contrast to prior studies, we split firms' R&D decision into two elements of 'whether to invest decision' and 'how much to invest decision'. The influences and mechanism of government subsidies on R&D decision are theoretically analysed to develop hypotheses tested in this study. We find that government subsidies have a promotion effect on both elements of the firms' R&D decision. Moreover, we also demonstrate the heterogeneous effects of government subsidies between state-owned and non-state firms. Due to the inherent principal-agent problem of state-owned firms and soft budget constraint, subsidies can only increase the probability to undertake R&D activities but cannot stimulate further investment in R&D efforts. However, our results indicate that government subsidies take effects in both elements of R&D decision for non-state firms.